Penguatan Pembelajaran Literasi Dasar Bagi Guru-Guru SD Se Kabupaten /Kota Jayapura - Yonggom, Aplonia D.; Ohee, Sara Marlina; Purba, Rispah; Ayomi, Golden; Hidayah, Hidayah (Universitas Cenderawasih, 2023)
This service activity is carried out for elementary school teachers spread across the district/city of Jayapura regarding basic literacy learning, specifically print awareness and alphabet knowledge so that they can deal with children's education problems from an early age when they are not yet in school or not yet literate. alphabet. The purpose of this community service activity is to provide reinforcement about applying basic literacy knowledge to teachers who are spread across several schools in both the city and Jayapura district. The implementation of socialization activities is carried out for one day and uses lecture and discussion methods as well as delivery of material/information, as well as providing exercises related to basic literacy learning in the development of elementary school children's lives, especially in terms of awareness of print awareness and introduction to how to teach the alphabet through the four stages of listening, say, read, and write. The number of participants involved was 24 people from the target of 30 participants. The results of the implementation of the socialization program in strengthening basic literacy went well and all participants were able to understand the importance of print awareness and teaching alphabet knowledge as well as ways and techniques for teaching it correctly.